Satisfacción laboral para la mejora del compromiso de los docentes de la carrera administración pública con la ESPAM MFL de Calceta - Intriago Intriago, Joselyn Alejandra (2019)
The Constitution of Ecuador in art. 26, establishes that education is a right of people throughout their lives and an inescapable and inexcusable duty of the State. It constitutes a priority area of public policy and state investment, guarantee of social equality and inclusion and an indispensable condition for good living. In this way, the Public Administration (AP) career originates the fulfillment of the right by incorporating trained teachers and researchers, for this reason the research was carried out on job satisfaction to improve the commitment of teachers, with the objective of evaluating said job satisfaction of The teachers of that career. For its fulfillment, activities were carried out to comply with the investigation, such as the description of the substantive processes of teachers, then an instrument was applied that allowed a diagnosis of the degree of job satisfaction of teachers, where an interview was conducted with the Director. Responsible for it specifying procedures incorporated into teaching activities; also a structured survey that facilitated obtaining results for the study such as: deficiency in the application of academic methods to achieve teaching effectiveness and disagreement about the work environment, allocation of economic resources for the development of scientific research. Finally, a plan was developed with improvement actions that seek to improve the job satisfaction of teachers given the description of beneficial results on the weaknesses found.